2017
DOI: 10.1002/2016jd025564
|View full text |Cite
|
Sign up to set email alerts
|

Potential impacts of urban land expansion on Asian airborne pollutant outflows

Abstract: Eastern part of China (EPC) has experienced rapid urbanization during the past few decades. Here we investigate the impacts of urban land expansion over EPC on the export of Asian pollutants to the western Pacific during January, April, July, and October of 2009 using the Weather Research and Forecasting model coupled to Chemistry (WRF/Chem) and a single‐layer urban canopy scheme. Over urbanizing areas, increases in the urban land fraction result in a linearly enhanced uplift of surface primary pollutants to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…To illustrate the impacts of EPT-current induced emissions reduction on air quality, we conduct additional model simulations using a well validated chemical transport model (WRF-Chem). The simulations are based on the latest available emission inventories of 2015 (Tao et al 2015(Tao et al , 2017. As shown in figure S139 in the supplementary information, the changes of regional concentrations of PM 2.5 and O 3 are largely proportional to their emissions reduction.…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate the impacts of EPT-current induced emissions reduction on air quality, we conduct additional model simulations using a well validated chemical transport model (WRF-Chem). The simulations are based on the latest available emission inventories of 2015 (Tao et al 2015(Tao et al , 2017. As shown in figure S139 in the supplementary information, the changes of regional concentrations of PM 2.5 and O 3 are largely proportional to their emissions reduction.…”
Section: Discussionmentioning
confidence: 99%
“…3, respectively). In the CTRL scenario, emissf NH 3 has been set to 2 as recent studies using top-down inverse modeling (Van Damme et al, 2018;Wang et al, 2018;Kong et al, 2019) and direct measurement (Wang et al, 2018) found that previous bottom-up inventories might underestimate the NH 3 emissions, and the MEIC inventory was estimated to underpredict NH 3 emissions by about 40 % over the North China Plain (Kong et al, 2019). As shown in Table S7 of the Supplement, compared to the scenario using the default MEIC emission data, the CTRL scenario (with doubled NH 3 emissions) better matches both the observed ammonia and ammonium concentrations at urban Beijing sites during wintertime (Meng et al, 2011;Liu et al, 2017;Song et al, 2018).…”
Section: Wrf-chem Model Configuration and Scenariosmentioning
confidence: 99%
“…The UHIE can exacerbate challenges associated with high temperatures in urban areas including (a) human health impacts from extreme heat, 1 such as heat stroke, heat exhaustion rates, and premature deaths; (b) daily total and peak air conditioning energy use during summer; 2 and (c) increases in urban ozone concentrations and potential influences on other air pollutants. 3,4 Several important environmental processes, which are driven by the effects of urban land expansion on surface-atmosphere coupling, can aggravate or mitigate the UHIE. First, widespread application of materials with high solar absorptance (e.g., asphalt concrete and many roofing materials) in urban areas increases absorption of solar energy.…”
Section: Introductionmentioning
confidence: 99%